Implementation of vancomycin dosing nomogram in an electronic prescribing system: an innovative tool in antibiotic stewardship - Tácio de Mendonça Lima; Sabrina Calil Elias; Rita de Cássia Elias Estrela; Fernando Luiz Lopes Cardoso (Universidade de São Paulo, 2014)
Vancomycin (VAN) is the gold standard therapy for Methicillin-resistant Staphylococcus aureus(MRSA) infections such as bacteremia and endocarditis. However, VAN suboptimal dosing for serious infections caused by S. aureus isolates that have elevated minimum inhibitory concentration (MIC), could be associated with poor outcome. Better understanding of VAN pharmacokinetics and pharmacodynamics (PK/PD) has led to the creation of new recommendations with optimized dosing regimens for the treatment of MRSA infections. For severe infectious, such as pneumonia and endocarditis, a VAN serum trough concentration of 15-20 mg/L at the steady state should be targeted. The aim of this study was to show how a nomogram with updated VAN dosing was devised and how it was implemented in the electronic prescribing (e-prescribing) system of a teaching hospital. VAN loading dose and maintenance doses were calculated from a pharmacokinetic equation using basic parameters: weight, estimated creatinine clearance, as well as peak and trough serum concentrations. The implementation of the VAN dosing nomogram in the hospital e-prescribing system definitively changed the long-standing medical prescription fallacy of "same dose fits all". Finally, this computer-based electronic program has allowed a wide-ranging intervention and should be recognized as a powerful tool for implementation in antimicrobial stewardship programs.